Digital-based Learning in Social Science Cluster Subjects in High School with Curriculum Merdeka - Octamaya Tenri Awaru, A.; Manda, Darman; Rasyid Ridha, M.; Darmayanti, Paramitha (KnE Social Sciences, 2024)
This study aims to evaluate digital-based learning in Social Sciences cluster subjects (sociology, geography, economics, history and civic education) in Senior High Schools with an independent curriculum. The research method used is descriptive with a quantitative approach. This descriptive research is used with the aim of knowing the value of independent variables without making comparisons or correlating with other variables. Data were collected through questionnaires developed based on key indicators of digital learning variables. The respondents of the study were teachers who taught social subjects and students who were taught. The results of the study found: The type of ICT used was 66.1%; the utilization rate of technology in learning is 82.6%; the level of student proficiency in the use of ICT technology is 73.4%; the level of teacher commitment to use ICT technology in learning is 76.1%; digital learning success rate is 77.0%. The teacher satisfaction rate was 74.9% and the student satisfaction rate was 88.8%. From this indicator data, it can be concluded that digital-based learning in social science cluster subjects in Senior High Schools in Makassar City is 77.0% or is in the very high category. Keywords: digital learning, social sciences